IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS BASED ON THE PERSPECTIVE OF MEDICAL RECORD AND HEALTH INFORMATION OFFICERS AT RSUD BALARAJA - Agustin, Rosalia; Putra, Daniel Happy; Sonia, Dina; Satrya, Bangga Agung (HEARTY, 2025)
This study examines the implementation of Electronic Medical Records (EMR) at Balaraja Regional Hospital from the perspective of medical recorders as the main users of the system. Digitalization of health services through EMR aims to improve efficiency and quality of service, but in its implementation there are still various obstacles, such as suboptimal infrastructure, use of hybrid systems, and limited training for officers. Using a descriptive qualitative method with the PIECES approach (Performance, Information, Economics, Control, Efficiency, and Service), this study involved 9 informants who were interviewed in depth. The results of the analysis show that EMR has increased the speed of data access, information accuracy, and work efficiency. However, challenges still arise in the form of double data entry, network disruptions, and lack of system integration. Although the system is considered quite secure in terms of access control, its effectiveness is still influenced by user readiness and compliance. In addition, user satisfaction with the system also depends heavily on system stability and ease of operation. This study recommends strengthening infrastructure, regular training, improving SOPs, and accelerating full digitalization so that the implementation of EMR can run optimally and sustainably.